Personnel safety with pressurized gas systems. Issue 4 (8th September 2016) - Cadwallader, Lee C.; Zhao, Haihua
Abstract : In this article, selected aspects of safety with compressed gas systems are discussed. Several accident case histories are described that illustrate the potential modes of injury from gas jets, pressure‐driven missiles, and asphyxiants. Using high‐pressure helium and nitrogen, estimates of safe exclusion distances to prevent skin injuries from gas leaks are calculated for differing pressures, temperatures, and breach sizes. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 330–336, 2016